2015
DOI: 10.4141/cjps-2015-114
|View full text |Cite
|
Sign up to set email alerts
|

Weed control in soybean using pyroxasulfone and sulfentrazone

Abstract: . 2015. Weed control in soybean using pyroxasulfone and sulfentrazone. Can. J. Plant Sci. 95: 1199Á1204. Pyroxasulfone and sulfentrazone are new herbicides currently being evaluated for weed control in soybean [Glycine max (L.) Merr.] in Ontario, Canada. Seven experiments were conducted over a 3-yr period (2011 to 2013) at Ridgetown and Exeter, Ontario, to evaluate weed management using pyroxasulfone, sulfentrazone and their tank-mixes relative to the industry standard, imazethapyr plus metribuzin. Tank-mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
1
17
0
2
Order By: Relevance
“…Results showed the effective broad‐spectrum weed control when premixes from Group 2 (ALS‐inhibitors), Group 5 (Photosystem II [PSII]‐inhibitors), Group 14 (protoporphyrinogen oxidase [PPO]‐inhibitors), and Group 15 (long‐chain fatty acid‐inhibitors) herbicides. Similarly, others reported that PRE application of PPO herbicides tank‐mixed with ALS‐inhibiting herbicides provided an effective control of broadleaf species (Belfry et al, 2015; Walsh et al, 2015); including kochia, Russian thistle ( Salsola tragus ), field bindweed ( Convolvulus arvensis ), velvetleaf, common lambsquarters, and yellow sweetclover ( Melilotus officinalis ) in Nebraska (Knezevic et al, 2009). Hausman et al (2013) also reported that PRE‐applied metribuzin and flumioxazin alone provided 92% waterhemp control at 60 DAPRE in soybean.…”
Section: Broadleaf Weed Controlmentioning
confidence: 97%
“…Results showed the effective broad‐spectrum weed control when premixes from Group 2 (ALS‐inhibitors), Group 5 (Photosystem II [PSII]‐inhibitors), Group 14 (protoporphyrinogen oxidase [PPO]‐inhibitors), and Group 15 (long‐chain fatty acid‐inhibitors) herbicides. Similarly, others reported that PRE application of PPO herbicides tank‐mixed with ALS‐inhibiting herbicides provided an effective control of broadleaf species (Belfry et al, 2015; Walsh et al, 2015); including kochia, Russian thistle ( Salsola tragus ), field bindweed ( Convolvulus arvensis ), velvetleaf, common lambsquarters, and yellow sweetclover ( Melilotus officinalis ) in Nebraska (Knezevic et al, 2009). Hausman et al (2013) also reported that PRE‐applied metribuzin and flumioxazin alone provided 92% waterhemp control at 60 DAPRE in soybean.…”
Section: Broadleaf Weed Controlmentioning
confidence: 97%
“…A associação de pyroxasulfone com sulfentrazone proporcionou ampliação do espectro de controle de plantas daninhas no caso de infestação de folhas largas como Amaranthus powellii e Abutilon theophrasti, quando comparado com tratamentos contendo os dois herbicidas isolados (Belfry et al, 2015), o que se assemelha aos resultados obtidos no presente trabalho.…”
Section: Resultsunclassified
“…Comumente são constatados casos de herbicidas seletivos a plantas de soja, mas não as plantas de feijão, tomando como exemplo os herbicidas chlorymuron-ethyl, cloransulam-methyl (Procópio et al, 2009) e pyroxasulfone (Soltani et al, 2009;Belfry et al, 2015a). Todavia, alguns herbicidas demostram seletividade a ambas as culturas, como é o caso do fomesafen e imazethapyr (Procópio et al, 2009).…”
Section: Resultsunclassified